Making Health Services More Accessible in Developing Countries Finance and Health Resources for Functioning Health Systems - Uchimura, Hiroko (Palgrave Macmillan UK, 2009)
Health is increasingly a critical concern in the context of development. This book examines the function of health systems, particularly the key factors: finance, human resources, pharmaceuticals, public facilities and stresses the importance of improving access to health services in developing countries